Efektivitas Pelayanan pada Partai Politik dan Organisasi Massa oleh Badan Kesatuan Bangsa dan Politik Kabupaten Seram Bagian Barat - TAIHUTTU, FRANS A.; UFIE, J.A. (Patria Artha Management Journal, 2022)
This study aims to determine the effectiveness of services to political parties and mass organizations at the National Unity and Political Agency of West Seram Regency, as well as to find out the obstacles and policies in achieving service effectiveness to political parties and mass organizations at the National Unity and Political Agency of Seram Regency. West. This study uses a quantitative and qualitative descriptive approach. The results of the questionnaire were processed descriptively using the frequency score, while the interviews were analyzed qualitatively to complete the results of the questionnaire or questionnaire. Based on the results of the analysis, it is known that services to political parties and mass organizations at the National and Political Unity Agency of West Seram Regency are in the quite effective category. One of the obstacles in achieving service effectiveness for political parties and mass organizations is that the apparatus resources both in terms of quality and quantity are still very limited. So that the policy that should be taken by the National Unity and Political Agency of Seram Regency is to increase the professionalism of the government apparatus in carrying out public service tasks, as well as improving the facilities and infrastructure of the apparatus.